Genetic variants with potential loss of function in Gyr, Girolando, and Guzerat cattle breeds by resequencing. - Stafuzza, N. B. [UNESP] (2017)
Univ Estadual Paulista, Dept Ciencias Exatas, Fac Ciencias Agr & Vet, Jaboticabal, Brazil